Pentingnya Peranan Pemerintah Daerah dalam Penyelenggaraan Pemilihan Umum - Maninggesa, Suwardi (Lembaga Yasin AlSys, 2022)
In the Indonesian state, the Constitution guarantees the sovereignty of the people, this is contained in article 2 paragraph (2) of the 1945 Constitution which states that